Anti-inflammatory effect and mechanism of action of Lindera erythrocarpa essential oil in lipopolysaccharide-stimulated RAW264.7 cells - Ko, Yeong-Jong; Ahn, Ginnae; Ham, Young-Min; Song, Sang-Mock; Ko, Eun-Yi; Cho, Su-Hyeon; Yoon, Weon-Jong; Kim, Kil-Nam (Technische Universität Dortmund, 2017)
The aim of this study was to investigate the chemical constituents of Lindera erythrocarpa essential oil (LEO) by gas chromatography-mass spectrometry and evaluate their inhibitory effect on the expression of pro-inflammatory mediators in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Fifteen compounds, accounting for 63.7 % of the composition of LEO, were identified. The main compounds were nerolidol (18.73 %), caryophyllene (14.41 %), α-humulene (7.73 %), germacrene-D (4.82 %), and α-pinene (4.47 %). LEO significantly inhibited the expression of inducible nitric oxide (NO) synthase and cyclooxygenase-2, and subsequent production of NO and prostaglandin E2. In addition, it reduced the release of pro-inflammatory cytokines in LPS-activated RAW264.7 cells. The molecular mechanism underlying the effect of LEO was associated with inhibition of the phosphorylation of mitogen-activated protein kinase (MAPK). Furthermore, LEO inhibited LPS-induced phosphorylation and degradation of inhibitor of kappa B-α, which is required for the activation of the p50 and p65 nuclear factor (NF)-κB subunits in RAW264.7 cells. Taken together, these data suggest that LEO exerted its anti-inflammatory effect by downregulating LPS-induced production of pro-inflammatory mediators through the inhibition of NF-κB and MAPK signaling in RAW264.7 cells.
EXCLI Journal;Vol. 16 2017
Keywords: Lindera erythrocarpa; Anti-inflammatory; Essential oil; NF- κ B; MAPK; 610